A simbologia dos metais e o universo do herói : um estudo sobre o escudo de Aquiles e o mito das raças - Souza, Leandro dos Santos (2021)
Our work proposes to make a literary analysis of the representativeness of the metals present in the construction of the images forged in the shield of Achilles that is found in chapter XVIII of Iliad. For the making of this, we propose a comparison between the description of Achilles‟s shield and the myth of the races found in Works and days of Hesiod. During our research, we noticed a symbolic and structural relationship between the texts, and starting from this point, we were successful in finding this similarity between the Homeric poem and the hesiodic one. Our analysis begins with the representation of the universe in which the hero is inserted, then it will rest on the myth of the races and their symbolic value according to the metals that represent them. From there, we established a parameter so that we could level both texts on the same subject, metals. Therefore, we made a counterpoint between the symbolism of the materials used in the forge of the Achilles shield and those presented by Hesiod in the myth of the creation of man. In this way, we were able to establish a parallel between them. Among the theorists covered in our study, we adopted as a basis, when it comes to the myth of races, the analysis of Jean Pierre Vernant found in his work Myth and Thought among the Greeks. To make references to the historical part, we chose to use Claude Mossé, as we saw the need to bring a historical panorama regarding the appearance of the Greek polis. Furthermore, since we decided to analyze symbolically the images present in the Achilles shield and the metals found in its construction, as well as those present in the description of the myth of the races, we brought to our discussion JR Forbes, in order to bring surfacing the significance of metals in Greece during the archaic and classical period. In terms of the symbolic, we decided to follow Northrop Frye, so that we could raise a discussion based on his notes on the subject. Considering, therefore, these theorists, we could see that the figure of the hero is inserted as a symbolic pillar, which when carrying the shield, takes over all the other races described by Hesiod.